Pengaruh Model Pembelajaran Discovery Learning Terhadap Kemampuan Literasi Matematis Siswa - Hia, Oidika Mawarni; Mendrofa, Ratna Natalia; Zega, Yulisman (Indo-MathEdu Intellectuals Journal, 2024)
This research is motivated by the preliminary study of researchers at UPTD SMP Negeri 1 Gunungsitoli Idanoi, which is so far students are less active and tend to be passive in the learning process and students' mathematical literacy skills are still low. The purpose of this research was to determine whether the discovery learning model effect the students' ability in mathematical literacy skills. This research was conducted at UPTD SMP Negeri 1 Gunungsitoli Idanoi with the research object at 8th grade students in the 2022/2023 academic year, which is consist of 7 classes with a total of 208 students. The samples in this research were VIII-F class as the experimental class which was consist of 28 students and VIII-G class as the control class which was 27 students. This research is quantitative research using a quasi-experimental research method (quasi experiment design). The research instrument used was a mathematical literacy test of five items for the pre-test and five items for the pos-test. The results of the study obtained t-count = 1,915 and t-table = 1.674. Because t-count > t-table is 1,915 > 1.674, then reject Ho accept Ha which means "there is an effect of the discovery learning model on students' mathematical literacy skills